Impact of reduced injected dose on the quantification of [18F]RO948 and [18F]Flortaucipir PET for in vivo tau pathology. (December 2021) - Young, Peter; Thomas, Wesley P.; Axelsson, Jan; Himmelmann, Jakob; Dominguez, Pablo Aguilar; Ohlsson, Tomas; Hansson, Oskar; Lubberink, Mark; Bohorquez, Sandra Sanabria; Rieckmann, Anna; Baker, Suzanne L.; Schöll, Michael
Abstract: Background: Previous research has demonstrated that the injected dose in PET examinations can be reduced without substantial effects on quantitative outcomes. These reductions can lead to lower radiation burden for subjects, reduced costs for institutions and potential for additional research scans of the same subject. Here, we investigated the effect of reduced injected doses of [ 18 F]RO948 and [ 18 F]Flortaucipir (FTP) on standardised uptake value ratios (SUVRs) and associated outcomes. Method: Images were manipulated from list‐mode data to simulate injected doses of 70%, 50%, 25% and 12.5% of the true injected dose. Initial analyses were scan time reduction for RO948 and dose reduction for FTP with future harmonisation of processing intended. Inferior cerebellum‐grey was used to compute SUVRs in regions‐of‐interest (ROIs) corresponding to the in vivo Braak regions of tau spread. Differences between true and reduced injected doses (given as a percentage) were calculated in individual regions as the mean of [SUVRreduced – SUVRtrue ] over the means of SUVRreduced and SUVRtrue values across subjects. Result: Previously reported test‐retest variability for RO948 and FTP are 2‐6% (±6%) and 1.5‐3.3% (±3%) respectively. Regionally, RO948 remained below this TRT variability at 25% injected dose, with an average SUVR difference of 2.3% (±8%) (figure 2), whereas FTP remained below TRT variability only at 70% injected dose with an average SUVR difference of 2.9% (±3%). However, differences were above TRT variability for FTP at lower injected doses. FTP average SUVR differences were observed to be higher in CN compared to AD patients at reduced injected doses but with greater variability in AD than CN. There were no differences observed between Ab+ and Ab‐ controls. Conclusion: Preliminary findings suggest that lower injected tracer‐doses for RO948 and FTP yield robust SUVRs. However, the degree to which injected doses can be reduced must be investigated further for different demographics and for different tracers. Ongoing work aims to harmonise the simulation list‐mode processing, add MCI/AD RO948 subjects, and evaluate dose reduction in [ 18 F]GTP1 data. Further validation will be performed against demographic and clinical variables, as well as for longitudinal data.